Penanaman Budaya Positif pada Karakter Religius di SMK Muhammadiyah 2 Kota Malang - Alya Dinia Asyfiqi Masykur (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe how a positive culture in schools is instilled through activities that have become a habit in schools. This study uses a qualitative approach with the type of case study research because it wants to explain in detail and explore more deeply about the implementation and implementation of a positive school culture, as well as the challenges and obstacles in the implementation and implementation of a positive school culture at SMK Muhammadiyah 2 Malang. The results of the study show that the school culture applied at SMK Muhammadiyah 2 Malang cannot be separated from character values, namely religious values, nationalist values, mutual cooperation values, independent character values, and integrity values. The school culture includes teachers guarding the gate to welcome students into school, reciting before starting learning, praying dhuha between breaks, students greeting and shaking hands when crossing paths with teachers, and not hesitating to help teachers when they need help